2020
DOI: 10.1029/2019wr026634
|View full text |Cite
|
Sign up to set email alerts
|

The Counteracting Effects of Snowmelt Rate and Timing on Runoff

Abstract: The declining mountain snowpack is expected to melt earlier and more slowly with climate warming. Previous work indicates that lower snowmelt rates are associated with decreased runoff. However, earlier snowmelt could increase runoff via lower vegetation water use in early spring. The relative importance of these factors with regard to runoff is linked to site‐specific conditions such as plant available water storage (PAWS) and energy availability. To disentangle the effects of snowmelt rate and timing on runo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 62 publications
1
25
0
Order By: Relevance
“…This pattern fits in part with Jeton et al (1996) where increased streamflow was associated with earlier water availability because vegetation may not be able to utilize water inputs early in the season due to phenological limitations. Barnhart et al (2020) also found that runoff from this site was more sensitive to changes in snowmelt timing than to changes in snowmelt rate and that earlier snowmelt resulted in increased runoff. The increase in streamflow by 2100 observed in Como Creek may be partially attributable to this process as we observed a 5 and 10 mm decrease in ET by 2100 under MP and LP scenarios, respectively, and an increase in streamflow (Table 3).…”
Section: Discussionmentioning
confidence: 77%
“…This pattern fits in part with Jeton et al (1996) where increased streamflow was associated with earlier water availability because vegetation may not be able to utilize water inputs early in the season due to phenological limitations. Barnhart et al (2020) also found that runoff from this site was more sensitive to changes in snowmelt timing than to changes in snowmelt rate and that earlier snowmelt resulted in increased runoff. The increase in streamflow by 2100 observed in Como Creek may be partially attributable to this process as we observed a 5 and 10 mm decrease in ET by 2100 under MP and LP scenarios, respectively, and an increase in streamflow (Table 3).…”
Section: Discussionmentioning
confidence: 77%
“…Annual streamflow is positively related to the percentage of total precipitation that falls as snow [83,84]; therefore, a decrease in snowfall fraction is expected to elicit a nonlinear hydrologic response. Additionally, an earlier onset of spring temperatures may not result in a detectably earlier spring freshet as energy limitations during late winter and early spring attenuate snowmelt rates [22,25] or weaken relationships between snowpack and spring hydrology [26,27]. Spring runoff should be monitored and evaluated for changes in magnitude and climatehydrologic coupling.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have detected an earlier spring freshet [23,24], there is not a simple linear relationship between rising temperatures, snowmelt, and hydrologic responses. Due to solar energy limitations during winter and early spring, rising temperatures and an earlier onset of above-freezing temperatures result in a slower rate of snowmelt [22,25], effectively weakening relationships between snowpack regimes and spring hydrology [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…For example, competing processes of canopy interception and sheltering from winds and solar radiation suggest forests with intermediate tree density promote greater snow accumulation and a later peak SWE (Broxton et al, 2015; Musselman et al, 2008). In turn, snow persistence has been found to produce more rapid snowmelt to induce soil saturation (Trujillo & Molotch, 2014), after which water can move vertically as recharge or laterally through the soil zone as interflow to promote more streamflow (Barnhard et al, 2020; Barnhart et al, 2016). Lateral movement of water is largely a function of soil storage and water holding capacity (Xiao et al, 2019) and initial soil moisture content, such that soil moisture observations can improve streamflow forecasts (Crow et al, 2018; Mahanama et al, 2012; Shahrban et al, 2018).…”
Section: Discussionmentioning
confidence: 99%